A Serological Biomarker of Laminin Gamma 1 Chain Degradation Reflects Altered Basement Membrane Remodeling in Crohn’s Disease and DSS Colitis - Lindholm, Majken; Di Sabatino, Antonio; Manon-Jensen, Tina; Mazza, Giuseppe; Madsen, Gunvor I.; Giuffrida, Paolo; Pinzani, Massimo; Krag, Aleksander; Karsdal, Morten A.; Kjeldsen, Jens; Mortensen, Joachim H. (Digestive diseases and sciences, 2022)
Background The laminin gamma 1 chain (LMγ1) is abundant along the crypt-villus axis in the intestinal basement membrane. Aims We investigated whether a serological biomarker of laminin degradation was associated with disease activity in patients with Crohn’s disease (CD) and in rats with dextran sulfate sodium (DSS)-induced colitis. Methods Serum samples from CD patients ( n = 43), healthy subjects ( n = 19), and Sprague Dawley rats receiving 5–6% DSS water for five days and regular drinking water for 11 days were included in this study. The LG1M biomarker, a neo-epitope degradation fragment of the LMγ1 chain generated by matrix metalloproteinases-9 (MMP-9), was measured in serum to estimate the level of laminin degradation. Results Serum LG1M was elevated in CD patients with active and inactive disease compared to healthy subjects ( p < 0.0001). LG1M distinguished CD patients from healthy subjects, with an area under the curve (AUC) of 0.81 ( p < 0.0001). Serum LG1M was decreased in DSS rats compared to controls 2 days after DSS withdrawal, and increased upon reversal of the disease. Conclusions Increased serum LG1M in active and inactive CD patients supports the evidence of altered LM expression in both inflamed and non-inflamed tissue. Moreover, lower LG1M levels in the early healing phase of DSS-induced colitis may reflect ongoing mucosal repair.